GOODBYE TO AFGHANS: What is the Promise of Human Rights to Human Rightslessness Afghan Migrants in Pakistan? - Hashimy, Sayed Qudrat (International Journal of Law in Changing World, 2024)
The Genealogies of complicity and struggle between Afghanistan and Pakistan date back to a single-page Agreement of 1893 (Duran line) and the invasion of the Union of Soviet Socialist Republics (USSR) in 1979. The squabble of the World towards Pakistan with its inglorious policy to deport undocumented 1.7 million refugees to a war-stricken country is inhuman and wrong and leaves them as political pawns. The Mass Exodus of Afghan Refugees and the anti-immigrant policy of Pakistan trigger some legal questions: Why is Pakistan deporting Afghans at this point? Who hears the voice of suffering at the dark noon? What happens next to these deportees? The existing article is poignant in examining the status of human rightslessness of sans-papiers under the human rights paradigm in Pakistan. In tandem with this, the paper also discusses the human rights dimension from the lens of the perplexing situation that prevails in Afghanistan. This article is percolated by axiomatic development in the theory and practice of human rights supplanted by wretched migrants. Thus, this paper offers a series of fragments of thought concerning some ways of understanding the changing human rights paradigms in Afghans. _________________________________ 阿富汗和巴基斯坦的联合与斗争可以追溯到1893年单页的《杜兰线协议》和1979年苏联的入侵。世界各国对巴基斯坦不光彩的政策表示不满，将170万无证件难民驱逐到一个战乱国家，这是不人道的错误，也是政治上的操作。阿富汗难民的大规模流亡和巴基斯坦的反移民政策引发了一些法律问题：为什么巴基斯坦在这个时候驱逐阿富汗人？谁在黑暗的正午听到了苦难的声音？这些被驱逐者接下来会发生什么？现有文章尖锐地审视了巴基斯坦人权范式下移民无人权的状态。与此同时，本文还从阿富汗普遍存在的复杂局势的角度检视了人权问题。本文加入了悲惨移民相关的人权理论与实践的公理化发展。因此，本文提供了一系列关于理解阿富汗人人权范式转变的思路。